Wireless vitals—Proof of concept for wireless patient monitoring in an emergency department setting. Issue 4 (13th December 2018) - Glasin, Joakim; Henricson, Joakim; Lindberg, Lars‐Göran; Wilhelms, Daniel
Abstract : Vital sign assessment is a common task in emergency medicine, but resources for continuous monitoring are restricted, data is often recorded manually, and entangled wires cause frustration. Therefore, we designed a small, wireless photoplethysmographic device capable of continuously assessing pulse, respiratory frequency and oxygen saturation on the sternum and tested the performance and feasibility in an emergency department setting. Fifty (56.3 ± 20.2 years), consenting emergency patients (29 male) were recruited. Heart rate, respiratory rate and oxygen saturation were recorded simultaneously using the device and standard monitoring equipment. Data was compared using Bland‐Altman plotting (heart rate, respiratory rate) and mean difference (oxygen saturation). The bias for heart‐ and respiratory rate was 0.4 (limits of agreements −11.3, 12.2 and −6.1, 7.0). Mean difference for oxygen saturation was −0.21 ± 2.35%. This may be the first wireless device to use photoplethysmography on the sternum for vital sign assessment. We noted good agreement with standard monitors, but lack of standardization in data processing between monitoring systems may limit the generalizability of these findings. Although further improvements are needed, the feasibility of this approach provides proof of concept for a new paradigm of large scale, wireless patient monitoring. Abstract : Vital sign assessment is a deceptively simple task and one of the most common procedures in an emergency department. Continuous monitoring is commonly restricted, and entangled wires are frustrating to patients and staff alike. Therefore, we designed a small, wireless photoplethysmographic device capable of assessing pulse, respiratory frequency and blood oxygen saturation on the sternum. We found good agreement with standard monitoring equipment.